Accuracy of adaptation total dentures made using CAD / CAM technology: a systematic review (Research, Society and Development, 2020)
Objective: Evaluate the accuracy of fitting total dentures made by technology using computer-aided design and manufacturing (CAD/CAM). Methodology: A systematic review of laboratory studies was carried out through the Medline-PubMed, Scopus, Scielo, Lilacs, Web of Science and Cochrane Library databases, using the descriptors: “Complete denture”, “Complete dentures”, “Total denture”, “Total dentures”, “Complete prosthesis”, “Complete prostheses”, “Total prosthesis”, “Total prostheses”, “Computer Aied Design”, “Computer Aied Manufacturing”, “CAD/CAM”, Adaptation” e “Precision”. Three calibrated reviewers obtained data and compared the results. All studies assessed the accuracy of fitting complete dentures made using CAD/CAM technology. This review followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-analyzes (PRISMA). Results: The strategy used for electronic and manual search resulted in 863 titles and abstracts. Of these, 10 were selected by the inclusion and exclusion criteria and read in full. At the end, 7 were elected for inclusion in the review. The selected studies have shown satisfactory results in relation to adaptation and effectiveness on prostheses made from the CAD/CAM process when compared to conventional methods. Conclusion: In vitro studies have shown that the complete denture manufacturing process by means of the CAD/CAM system presents better adaptation accuracy when compared to the conventional method. The milling method showed superior results when compared to 3D printing.